Redemption of Minority Shares and Related Fair Price Determination in the Finnish Legal System - Elonen, Otto (Udayana Journal of Law and Culture, 2022)
The Finnish Limited Company Act includes many situations where a redemption of a share is possible. However, this article focuses on examining situations where a redemption of a share results from a concentration of control in a company by a single party and analyze how the redemption price is determined. This is because the regulation in Chapter 18 of the Finnish Limited Company Act on the redemption of shares on the basis of a concentration of control is unclear. Finnish Limited Company Act determines that the price to be paid out for redemption of a share must be “fair price”. Therefore, the meaning of fair price becomes a central issue to be discussed. It identifies factors and specific reasons influence the formation of the fair price in some of the situations that may come in question. The subject is mainly approached from a legal perspective, but also from an economic theoretical point of view. This article also presents a number of different share valuation methods and how they should be used to determine the fair price. Legal argumentation and interpretation are developed based on legislation, government proposals (draft of Act), and case law, since they provide a framework for the valuation process. However, the final conclusion of the article suggests that there is no unambiguous answer as to what constitutes a fair price, as its determination depends on many variables.